Respuesta :

Answer:

[tex] 5\bigg(x-\frac{3}{2}\bigg)^2-\frac{41}{4}[/tex]

Step-by-step explanation:

  • [tex] 5x^2-15x +1[/tex]

  • [tex]= 5\bigg(x^2-3x +\frac{1}{5}\bigg)[/tex]

  • [tex] =5\bigg[x^2-2.\frac{3}{2}x +\bigg(\frac{3}{2}\bigg)^2-\bigg(\frac{3}{2}\bigg)^2+\frac{1}{5}\bigg][/tex]

  • [tex] =5\bigg[\bigg(x-\frac{3}{2}\bigg)^2+\frac{1}{5}-\frac{9}{4}\bigg][/tex]

  • [tex] =5\bigg[\bigg(x-\frac{3}{2}\bigg)^2+\frac{4-45}{20}\bigg][/tex]

  • [tex] =5\bigg(x-\frac{3}{2}\bigg)^2-5.\frac{41}{20}[/tex]

  • [tex] =5\bigg(x-\frac{3}{2}\bigg)^2-5.\frac{41}{20}[/tex]

  • [tex] =5\bigg(x-\frac{3}{2}\bigg)^2-\frac{41}{4}[/tex]
ACCESS MORE